Factors influencing beef cattle marketing behavior in pastoral areas of Kenya: the role of livestock market information - Komen, M.; Kariuki, G.; Kaitho, R. (GL-CRSP, 2009)
Marketing transactions take place in an environment where information is shared and exchanged among and between sellers, buyers and middlemen. It is argued that traders and middlemen have a competitive advantage over producers in negotiating for prices, because the former have access to prices in both primary and terminal markets, while the latter only have limited access to prices in the primary markets. This Research Brief highlights the situation regarding access to livestock marketing information by producers in pastoral markets of Kenya. Results show that livestock marketing information was not accessible to producers from September 2004 to September 2005, and hence did not play a significant role in influencing market prices. Subsequent analyses also show that producers consider a number of attributes when pegging prices to their animals, and that these tally with the categorization system developed by the Livestock Information Network and Knowledge System (LINKS) project. Further findings suggest that past efforts to develop livestock marketing information systems have been dogged by limited capacity to provide information that is accurate, timely, reliable, and spatially coherent. This has been exacerbated by failure to effectively use existing media and complement these with emerging information communication technologies to disseminate the information. LINKS has since responded to these factors through improvements in geographical coverage, accuracy, reliability and timeliness in the overall livestock market information system, as well as through improved information dissemination systems; improvements that have strengthened LINKS, allowing it to function as the foundation for the National Livestock Marketing Information System in Kenya.